2014
DOI: 10.7903/cmr.12012
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intention and Outcome Expectancy: Evidence from South Korea and China

Abstract: Focusing on the East Asian context, this study examines (1) cultural and gender differences in entrepreneurial intention, (2) the mediating effects of culture and gender on the relationships between entrepreneurial intention and expectancies of positive entrepreneurial outcomes, and (3) the results of entrepreneurial intention of females. The findings reveal that while Chinese students have a greater entrepreneurial intention than South Korean students, the relationships between entrepreneurial intention and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…This clearly shows that exposing individuals to various forms of experience and knowledge can help them improve their ability to exploit entrepreneurial opportunities. This is consistent with previous studies that indicated entrepreneurship education can increase a student's ability and his/her tendency to engage in entrepreneurship (Jiang & Wang, 2014;Lackeus 2015;Othman & Othman, 2015;Sanchez & Sahuquillo, 2018). This is acknowledged by Li & Wu (2019) that students who have completed an entrepreneurship module or entrepreneurship course are more possible to choose an entrepreneur career than students who do not.…”
Section: Discussionsupporting
confidence: 92%
“…This clearly shows that exposing individuals to various forms of experience and knowledge can help them improve their ability to exploit entrepreneurial opportunities. This is consistent with previous studies that indicated entrepreneurship education can increase a student's ability and his/her tendency to engage in entrepreneurship (Jiang & Wang, 2014;Lackeus 2015;Othman & Othman, 2015;Sanchez & Sahuquillo, 2018). This is acknowledged by Li & Wu (2019) that students who have completed an entrepreneurship module or entrepreneurship course are more possible to choose an entrepreneur career than students who do not.…”
Section: Discussionsupporting
confidence: 92%
“…Cross-country comparative studies of women entrepreneurs show that even within similar societal cultural contexts, Chinese women display different attitudes than their counterparts outside China in terms of entrepreneurial intention (e.g. Bickenbach, Dohse, and Liu 2014;Jiang and Wang 2014). For example, Jiang and Wang (2014, 251) comparative study of entrepreneurial intention between Chinese and Korean female students showed that 'while Chinese students have a greater entrepreneurial intention than South Korean students, the relationships between entrepreneurial intention and outcome expectancies are stronger in South Korean than in Chinese students.…”
Section: The Role Of Societal Culturementioning
confidence: 99%
“…Specifically, the body of research on women entrepreneurship in China has been conducted from four main theoretical perspectives: (1) the institutional perspective that examines the institutional environment at the macro level; (2) the cultural perspective that accentuates the impact of societal culture and gender norm on Chinese women's attitudes towards work-family and business management (e.g. Jiang and Wang 2014;Tan 2008;Zhu, Kara, and Zhu 2019); (3) the resource-based/resource-dependence perspective that focuses on the resources of/required from individual entrepreneurs (e.g. financial, human and social capital, political connections and family support) (e.g.…”
Section: Theoretical Angles Of Research On Women Entrepreneurshipmentioning
confidence: 99%
“…They were also better users of the social media in communicating their respective accomplishments and sharing their experiences (Dewey & Keally, 2008). This reflects on both their job-career prospects as well as their qualifications and attraction to the work domains (Jiang & Wang, 2014). Managerially, this means that female employees seeking a promotion in their career were more prone to improve their educational level in order to increase their chances of reaching the targeted position through the classical HR employability dimensions (Beheshtifar et al, 2012) and performance-related assessment (Nilssson & Ellström, 2012).…”
Section: Results Analysis and Implicationsmentioning
confidence: 98%